Lateral Reactive Infiltration in a Vertical Gabbroic Crystal Mush, Skaergaard Intrusion, East Greenland - Namur, Olivier; Humphreys, Madeleine C. S.; Holness, Marian B. (Journal of Petrology, 2013)
The Marginal Border Series of the Skaergaard intrusion (East Greenland) crystallized in situ on the vertical walls of the magma chamber. It is subdivided into an outer Unbanded Division and an inner Banded Division. The Banded Division contains abundant centimetre- to decimetre-thick bands dominated by fine-grained mafic minerals, with a morphology evolving from almost planar to deeply scalloped and fingered with increasing distance from the intrusion margin. The morphology of these bands is reminiscent of the reaction fronts described in sedimentary basins infiltrated by reactive fluids. We propose that the banding in the Skaergaard Marginal Border Series is produced by chemical disequilibrium resulting from the suction of primitive liquid from the main magma body into the crystal mush, driven by shrinkage of the mush during solidification. Liquid porous flow results in partial dissolution of evolved pre-existing mafic minerals in the mush. This changes the mush liquid composition to one capable of crystallizing mafic rocks with a very minor plagioclase component. Abrupt solidification of this liquid, resulting in the formation of the colloform bands, is explained by supersaturation of some mafic mineral components (e.g. olivine, clinopyroxene, Fe–Ti oxides) in the infiltrating melt. We suggest that the morphological evolution of the colloform bands is a consequence of increasing crystal mush thickness with progressive differentiation.